Enhancing Strength of Bamboo using GFRP and PU - Mohamad Nor, Norazman; Hui Xin, Teoh; Mohammed Alias Yusof (International Journal of Sustainable Construction Engineering and Technology, 2020)
Bamboo is an eco-friendly material, it can be used in various applications such as bamboo housing, bamboo bridges, bamboo scaffolding, ply bamboo, bamboo furniture, and for defence applications. It has various advantages to be used as structural material. However, it has weaknesses such as crushing failure under extreme loading that need to be addressed. The objective of this research is to enhance bamboo bearing and bending capacity using various stiffeners.  Experimental work done is to investigate the compressive strength, bending strength, bearing strength and tensile strength of raw local bamboo. Further analysis includes bending and bearing strength of raw bamboo and strengthen bamboo using Glass Fiber Reinforced Polymer (GFRP) and Polyurethane (PU) Foams. From the test done, the bearing strength of raw bamboo Semantan with node is between 2.61 MPa to 3.14 MPa and for raw bamboo Semantan without node is between 0.28 MPa to 0.82 MPa, average bending strength of raw bamboo Semantan is 59 MPa. For strengthen bamboo with 4 layers of Glass Fiber Reinforced Polymer, the bearing strength without node is between 1.59 MPa to 2.38 MPa, and the average bending strength is 62 MPa which is about 5% higher than raw bamboo.Keywords: Bamboo Semantan, Strengthening Bamboo, Glass Fiber Reinforced Polymer (GFRP), Defence Structure, Green Building (GBI)